2014
DOI: 10.1007/s10750-014-2000-8
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on body size of freshwater crustacean zooplankton from Greenland to the tropics

Abstract: The body size of zooplankton has substantive effects on the function of aquatic food webs because size affects the ability of zooplankton to: exploit food resources, effectively clear the water of algae, and serve as a food source for fish. A variety of factors may affect size, and earlier studies indicate that water temperature may be a particularly important variable. Here we tested the hypothesis that the body size of cladocerans, calanoids and cyclopoids declines with increasing water temperature, a respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 36 publications
3
47
0
Order By: Relevance
“…According to these authors, the highest mean sizes were observed between 6°C and 8°C, declining at higher or lower temperatures. Havens et al (2015), comparing 122 lakes located from 6° to 74°N and from 19° to 21°S, showed a relationship between size (as weight) of cladocerans and cyclopoid copepods and temperature. In contrast, Iglesias et al (2011) suggested that predation by fish is the major factor explaining the smaller size of zooplankton in warm lakes.…”
Section: Introductionmentioning
confidence: 98%
“…According to these authors, the highest mean sizes were observed between 6°C and 8°C, declining at higher or lower temperatures. Havens et al (2015), comparing 122 lakes located from 6° to 74°N and from 19° to 21°S, showed a relationship between size (as weight) of cladocerans and cyclopoid copepods and temperature. In contrast, Iglesias et al (2011) suggested that predation by fish is the major factor explaining the smaller size of zooplankton in warm lakes.…”
Section: Introductionmentioning
confidence: 98%
“…Fish predation is apparently even stronger in warm lakes than in comparable temperate lakes [19][20][21]; the fish communities in warm lakes typically have higher densities, greater taxonomic and trophic diversity (with predominance of omnivores) and smaller body size [22,23]. Experimental studies have elucidated the effect of planktivorous fish predation on zooplankton communities in subtropical and Mediterranean shallow lakes [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However, this is common among fishless, saline lakes in Central Argentina. These lakes are inhabited by the crustaceans B. poopoensis and M. eugeniae and by the rotifers Hexarthra fennica and Brachionus plicatilis (Vignatti, 2011;Vignatti et al 2012a;2012b;2016; Echaniz, 2010; Echaniz et al 2006; 2013a; 2013b;2015;2016). Whereas these crustacean species are endemic to Neotropical halophilic lakes, the rotifers are cosmopolitan and are broadly distributed given their wide tolerance to salinity (Fontaneto et al 2006;Echaniz et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in ectotherm vertebrates, individuals of small size are likely to occur at lower environmental temperatures (Gillooly et al 2002;Ohlberger, 2013), in zooplankton animals, such as cladocerans (Havens et al 2015) and copepods (Anufriieva & Shadrin, 2014), larger body sizes have been registered at lower temperatures. In the present study, the observed increase in body size for B. poopoensis and M. eugeniae is a likely consequence of the stress produced by increased salinity rather than that of low temperatures (Herbst, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation